Nicaragua : Unfinished Revolution - Rosset, Peter | Vandermeer, John (Estados Unidos | ESTADOS UNIDOS Grove Press, New York, 1986)
Since publication of the first nicaragus Reader in 1983, the pattern of tension and hostility between the gvernments of the united states and nicaragua las intensified.
Sin Especificar
Keywords: Nicaragua-Historia-1979-1990 | Contra revolución-Nicaragua | Política y gobierno-Nicaragua | Relaciones exteriores-Estados Unidos